Phenotyping asthma, rhinitis and eczema in MeDALL population‐based birth cohorts: an allergic comorbidity cluster. Issue 8 (20th May 2015) - Garcia‐Aymerich, J.; Benet, M.; Saeys, Y.; Pinart, M.; Basagaña, X.; Smit, H. A.; Siroux, V.; Just, J.; Momas, I.; Rancière, F.; Keil, T.; Hohmann, C.; et al.
Abstract Background Asthma, rhinitis and eczema often co‐occur in children, but their interrelationships at the population level have been poorly addressed. We assessed co‐occurrence of childhood asthma, rhinitis and eczema using unsupervised statistical techniques. Methods We included 17 209 children at 4 years and 14 585 at 8 years from seven European population‐based birth cohorts (MeDALL project). At each age period, children were grouped, using partitioning cluster analysis, according to the distribution of 23 variables covering symptoms 'ever' and 'in the last 12 months', doctor diagnosis, age of onset and treatments of asthma, rhinitis and eczema; immunoglobulin E sensitization; weight; and height. We tested the sensitivity of our estimates to subject and variable selections, and to different statistical approaches, including latent class analysis and self‐organizing maps. Results Two groups were identified as the optimal way to cluster the data at both age periods and in all sensitivity analyses. The first (reference) group at 4 and 8 years (including 70% and 79% of children, respectively) was characterized by a low prevalence of symptoms and sensitization, whereas the second (symptomatic) group exhibited more frequent symptoms and sensitization. Ninety‐nine percentage of children with comorbidities (co‐occurrence of asthma, rhinitis and/or eczema) were included in the symptomatic group at both ages. The children's characteristics in both groups were consistent in all sensitivity analyses. Conclusion At 4 and 8 years, at the population level, asthma, rhinitis and eczema can be classified together as an allergic comorbidity cluster. Future research including time‐repeated assessments and biological data will help understanding the interrelationships between these diseases.